PHLPP1 promotes neutral lipid accumulation through AMPK/ChREBP-dependent lipid uptake and fatty acid synthesis pathways - Balamurugan, Keerthana; Medishetti, Raghavender; Kotha, Jyothi; Behera, Parameshwar; Chandra, Kanika; Mavuduru, Vijay Aditya; Joshi, Manjunath B.; Samineni, Ramesh; Katika, Madhumohan R.; Ball, Writoban Basu; Thondamal, Manjunatha; Challa, Anil; et al. (iScience, 2022)
Infiltration of arterial intima by foamy macrophages is a hallmark of early atherosclerotic lesions. Here, we investigated the potential role of Ser/Thr phosphatase PHLPP1 in foam cell development. PHLPP1 levels were elevated in OxLDL-exposed macrophages and high-fat diet (HFD)-fed zebrafish larvae. Using overexpression and knockdown approaches, we show that PHLPP1 promotes the accumulation of neutral lipids, and augments cellular total cholesterol and free fatty acid (FFA) levels. RNA-Seq analysis uncovered PHLPP1 role in lipid metabolism pathways. PHLPP1 interacted with and modestly increased ChREBP recruitment to Fasn promoter. PHLPP1-mediated lipid accumulation was attenuated by AMPK activation. Pharmacological inhibition or CRISPR/Cas9-mediated disruption of PHLPP1 resulted in lower lipid accumulation in the intersegmental vessels of HFD-fed zebrafish larvae along with a reduction in total cholesterol and triglyceride levels. Deficiency of phlp-2, C. elegans PHLPP1/2 ortholog, abolished lipid accumulation in high cholesterol-fed worms. We conclude that PHLPP1 exerts a significant effect on lipid buildup. [Display omitted] •PHLPP1 levels are elevated in OxLDL exposed macrophages and HFD-fed zebrafish larvae•Loss of PHLPP1 reduces neutral lipid build-up in macrophages, zebrafish, and C. elegans•PHLPP1 impairs pathways linked to lipid metabolism and inflammation•PHLPP1-dependent lipid build-up involves AMPK and ChREBP pathways Biological sciences; Lipid; Molecular physiology; Molecular biology